UPGRADING PROCESS FINISHING GRAIN CRACKS ON COW CRUST LEATHER CORRECTED GRAIN BOX UPPER ARMY SHOES - Wahyu Fajar Winata; Nabilla Indrakusuma; Nais Pinta Adetya (Politek ATK Yogyakarta Press, 2023)
Crust-dyed leather is a product that has gone through the process of beam house operation, tanning, and post-tanning but has not gone through finishing. The purpose of this study is to overcome these problems by upgrading the finishing process to cover broken grain defects. The raw material used is rejected quality crust cowhide leather with 1 side broken grain defects. The finishing process upgrading method used to overcome this problem is buffing using 240-size sandpaper to erode broken grain parts to make them more disguised and impregnation with water, acrylic polymer (2350 RE), and penetrator (Biofin AU BK) 64). The impregnation solution can coat the cracked crust grain parts by forming new grains which have high shatter resistance properties. The results of leather testing after upgrading were carried out at the Rubber and Plastic Leather Center, Yogyakarta, obtained results that were following ISO 3379: 2015 standards, namely distension of grain at a crack of 8.60 mm and grain crack load of 467.28 N. It can be concluded that the buffing and impregnation in upgrading the finishing process can overcome the problem of cracked CGB upper army shoe grain crust cow skin and has met the burst resistance test standard ISO 3379:2015.